Performance investigation of a novel polygeneration system based on liquid air energy storage. (1st February 2023) - Esmaeilion, Farbod; Soltani, M.; Dusseault, M.B.; Rosen, Marc A.
Highlights: Introduction of a novel polygeneration system for power, heating, cooling, freshwater, hydrogen, and NaClO production based on LAES. Energy, exergy, economic, and exergoenvironmental studies are conducted. Environmental problems are considerably alleviated by converting brine to hydrogen and NaClO. Abstract: Energy storage systems are important in polygeneration systems, as they help them attain sustainable performance concerning technical, economic, and environmental factors. In this work, a novel polygeneration system based on liquid air energy storage (LAES) and a multi-stage flash (MSF) desalination system is designed. To provide a comprehensive understanding of the system operation and behavior, energy, exergy, economic, and exergoenvironmental assessments are conducted. The proposed polygeneration system is able to provide electrical energy, heating, cooling, sodium hypochlorite, hydrogen, and freshwater. The overall system has three main subsystems: LAES, combined cooling, heat & power (CCHP) unit, and multi-stage flash desalination system. Energy and exergy analyses are carried out and show that the round-trip efficiencies based on energy and exergy are 63.6 % and 61 %, respectively. Also, the annual production values for the hydrogen, potable water, and sodium hypochlorite are 10.2 × 10 5 m 3, 4.8 × 10 3 m 3, and 43.2 tones, respectively. From an economic point of view, the payback period and internal rate of return are 3.4 years and 0.32, respectively. Finally, the exergoenvironmental study shows that the factors for environmental damage effectiveness, exergoenvironmental, exergy stability, and sustainability index for the proposed system are 3.43, 1.68, 0.7, and 1.96.